FNDC5 (irisin) gene and exceptional longevity: a functional replication study with rs16835198 and rs726344 SNPs - Sanchis-Gomar, Fabian (Age (Dordr), 2014)
Irisin might play an important role in reducing the risk of obesity, insulin resistance, or several related diseases, and high irisin levels may contribute to successful aging. Thus, the irisin precursor (FNDC5) gene is a candidate to influence exceptional longevity (EL), i.e., being a centenarian. It has been recently shown that two single-nucleotide polymorphisms (SNPs) in the FNDC5 gene, rs16835198 and rs726344, are associated with in vivo insulin sensitivity in adults. We determined luciferase gene reporter activity in the two above-mentioned SNPs and studied genotype distributions among centenarians (n = 175, 144 women) and healthy controls (n = 347, 142 women) from Spain. We also studied an Italian [79 healthy centenarians (40 women) and 316 healthy controls (156 women)] and a Japanese cohort [742 centenarians (623 women) and 499 healthy controls (356 women)]. The rs726344 SNP had functional significance, as shown by differences in luciferase activity between the constructs of this SNP (all P ≤ 0.05), with the variant A-allele having higher luciferase activity compared with the G-allele (P = 0.04). For the rs16835198 SNP, the variant T-allele tended to show higher luciferase activity compared with the G-allele (P = 0.07). However, we found no differences between genotype/allele frequencies of the two SNPs in centenarians versus controls in any cohort, and no significant association (using logistic regression adjusted by sex) between the two SNPs and EL. Further research is needed with different cohorts as well as with additional variants in the FNDC5 gene or in other genes involved in irisin signaling.